Glu298Asp (rs1799983) Polymorphism Influences Postprandial Vascular Reactivity and the Insulin Response to Meals of Varying Fat Composition in Postmenopausal Women: Findings from the Randomized, Controlled Dietary Intervention and VAScular function (DIVAS)-2 Study. Issue 4 (9th March 2021) - Rathnayake, Kumari M; Weech, Michelle; Lovegrove, Julie A; Jackson, Kim G
ABSTRACT: Background: Previous acute studies suggest the Glu298Asp polymorphism (rs1799983) may influence vascular reactivity in response to long-chain n–3 PUFA intake. However, the effects of this genotype on postprandial vascular function after meals rich in SFAs, n–6 PUFAs, and MUFAs are unclear. Objectives: This study determined the impact of the Glu298Asp polymorphism on changes in vascular function and cardiometabolic risk biomarkers in response to sequential meals of varying fat composition. Methods: In a randomized, double-blind, crossover, acute study, 32 postmenopausal women (mean ± SD age: 58 ± 5 y; BMI: 25.9 ± 4.1 kg/m 2 ) consumed mixed meals (breakfast: 0 min, 50 g fat; lunch: 330 min, 30 g fat) containing SFAs, n–6 PUFAs, or MUFAs on 3 occasions. Blood samples for cardiometabolic disease risk markers and real-time measures of vascular reactivity [including flow-mediated dilatation (FMD; primary outcome)] were collected/performed before and regularly for 480 min after breakfast. Participants were retrospectively genotyped for the Glu298Asp (rs1799983) polymorphism. Data were analyzed using linear mixed models. Results: For the postprandial %FMD response, a test fat × genotype interaction was observed for the AUC ( P = 0.019) but not incremental AUC (IAUC), with the AUC being ∼24% greater after MUFA- than after SFA- and n–6 PUFA–rich meals in the Glu298 homozygotes ( P ≤ 0.026). Test fat × genotype interactions were also evident for postprandial insulin ( P ≤ 0.005), with the MUFA-rich meals demonstrating significantly higher AUC (12.8%/14.9%), IAUC (14.6%/20.0%), and maximum concentration (20.0%/34.5%) than the SFA- and n–6 PUFA–rich meals, respectively, in Asp298 carriers ( P < 0.05). Genotype did not influence other study outcome measures in response to the test fats. Conclusions: Our findings suggest the Glu298Asp polymorphism may represent a potential determinant of the inter-individual variability in postprandial responsiveness of %FMD and insulin to acute meal fat composition in postmenopausal women. Further studies are required to confirm these observations. This trial was registered at clinicaltrials.gov as NCT02144454.